Juridical Analysis of Fundamental Considerations of The Judge on Defendant’s Attitude at The Trial - Adi Rachmat, Bayu; Waluyo, Bambang (JURNAL USM LAW REVIEW, 2023)
This research aims to determine the relevance of the principle of judicial independence in deciding or considering the judge's verdict on the defendant in criminal cases under trial. It also aims to identify the legal basis that judge used in delivering the verdict. This study used a normative research method, from various legal principles, legal systems, and statutory regulations. The specific case under investigation involved an issue of injustice that occurred during the trial, where the judge granted leniency to the defendant based on their courteous behavior during the trial. The focus of this research is on aspects that may be considered for leniency by the judge, one of which is the defendant's polite behavior during the trial. Polite behavior is not explicitly regulated in criminal law, making it necessary to further investigate the judge's considerations in granting leniency to defendants who behave politely during the trial. This research is based on Law Number 48 of 2009 concerning the judiciary.